Yahoo Answers จะปิดใช้งานในวันที่ 4 พฤษภาคม 2021 (เวลาตะวันออก) แล��ตอนนี้เว็บไซต์ Yahoo Answers จะอยู่ในโหมดอ่านอย่างเดียว คุณสมบัติหรือบริการอื่นๆ ของ Yahoo หรือบัญชี Yahoo ของคุณจะไม่มีการเปลี่ยนแปลงใดๆ คุณสามารถค้นหาข้อมูลเพิ่มเติมเกี่ยวกับการปิดใช้งาน Yahoo Answers และวิธีการดาวน์โหลดข้อมูลของคุณในหน้าความช่วยเหลือนี้
Can you explain why this series conditionally convergent?
The series (-1)^(k+1)*(k+7)/(k(k+4)) from k=1 to infinity is conditionally convergent
Can you show me why? I know that the series converges but diverge absolutely
I just need to know what tests i have to use and how
Please show me all the steps/ Thanks!
2 คำตอบ
- ?Lv 77 ปี ที่ผ่านมา
T(k)=(k+7)/[k(k+4)]=>
T(k+1)=(k+8)/[(k+1)(k+5)]
T(k)-T(k+1)=
(k+7)/[k(k+4)]-(k+8)/[(k+1)(k+5)]=
(k^2+15k+35)/[k(k+1)(k+4)(k+5)]>0
(since k>=1)
=>
T(k)>T(k+1)=>
the terms in the series are decreasing
in the absolute value & T(k)->0 as k->inf.
The series is an alternating decreasing
series=>it converges conditionally.
(You can find the theorem in a math-book
supporting this conclusion, the Leibnitz's Test ).
|T(k+1)/T(k)|=k(k+8)(k+4)/[(k+1)(k+5)(k+7)]=>
|T(k+1)/T(k)|-1=
-(k^2+15k+35)/(k^3+13k^2+47k+35)
ln(k)[-(k^2+15k+35)/(k^3+13k^2+47k+35)]=
-ln(k)/[(k^3+13k^2+47k+35)/(k^2+15k+35)]=g(k)
limit g(k)=
k->inf.
limit { -1/{k[(k^4+21k^3+...-35)]/(k^2+15k+35)^2}}
k->inf.
=0=>the series diverges absolutely.
This test is known as Bertrand's Test.
- kbLv 77 ปี ที่ผ่านมา
(i) Σ(k=1 to ∞) (-1)^(k+1) (k+7)/(k(k+4)) converges by the Alternating Series Test, since {(k+7)/(k(k+4))} is a decreasing sequence which converges to 0.
To show the 'decreasing' part, note that
(d/dk) (k+7)/(k(k+4))
= (d/dk) (k+7)/(k^2+4k)
= [(k^2+4k) - (k+7)(2k+4)] / (k^2+4k)^2
= -(k^2+14k+28) / (k^2+4k)^2
< 0 for all k > 0.
-------
(ii) Σ(k=1 to ∞) |(-1)^(k+1) (k+7)/(k(k+4))|
= Σ(k=1 to ∞) (k+7)/(k(k+4)) diverges by the Comparison Test.
To show this, note that for all k > 0:
(k+7)/(k(k+4)) > (k+4)/(k(k+4)) = 1/k, and Σ(k=1 to ∞) 1/k is the divergent p-series.
Hence, Σ(k=1 to ∞) (-1)^(k+1) (k+7)/(k(k+4)) is conditionally convergent.
-------
I hope this helps!